Literacy as Epistemology and Educational Policy: An Exploration of a Large Swedish Professional Development Programme for Teachers - Maria Löfgren (Taylor & Francis Group, 2023)
ABSTRACTFrom once being synonymous with reading and writing, literacy, as a concept has expanded in the last three decades to today being associated with multiple meaning making forms and competences. Impactful, in this shift, has been the research orientation of New Literacy Studies. Besides academia, the literacy concept has also had a major influence on the global assessment frameworks of Program for International Student Assessment (PISA) and Progress in International Reading Literacy Study (PIRLS). This study is interested in the epistemological potential of this perception of literacy, but also on how it affects educational policy. Material examined is a large Swedish governmentally-initiated professional development programme for teachers, launched in 2014. Two main variants of the literacy concept can be identified in the programme, one more closely aligned with New Literacy Studies, and the other more influenced by PISA and PIRLS. Findings show, strong impact from the global assessment version of the literacy concept, resulting in a mainly skills-based and instrumental educational discourse, far from the concept of Bildung, traditionally characteristic of the Nordic school systems. Further, of the two variants, New Literacy has a broader epistemological potential, and is, as such, more closely related to Bildung.